Kepemimpinan Kepala Madrasah dalam Peningkatkan Motivasi Kerja Guru di MA Al-Mahrusiyah Lirboyo Kediri - Ali Mustofa; Muhammad Abdul Alim (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2021)
KThe head of a madrasa is a person who leads an educational institution where one of the duties is a Motivator. The results showed that: The principal of madrasah increased teacher motivation. Namely a) Motivating morale through providing good infrastructure in accordance with the capabilities of the madrasah and holding general recitation, b) Creating togetherness between teachers and friends. c) Disciplinary fostering, this is done through meetings or deliberations with teachers and employees. d) Giving awards this is done through giving praise and giving gifts or rewards to teachers who are considered to have achievements. e) Creating security in the environment. f) Building active and creative working groups. g) Developing the teaching profession. The inhibiting factor arises from the existence of personal problems in terms of personality such as from the side of his family, the learning that comes in the morning and those that enter the afternoon, must know the ability of each teacher so that when giving assignments according to their abilities, each person's behavior is different so they must also respond in different ways. , the morale of the teachers is sometimes great, sometimes it also decreases. The supporting factors are: Always motivating and motivating each other, providing facilities, and understanding the differences in the character of each teacher.